SUPPLEMENT TO THE PHYTOGEOGRAPHICAL STUDIES OF THE RARE AND INTERNATIONALLY SIGNIFICANT SPECIES IN THE FLORA OF SERBIA, KOSOVO AND METOHIJA NORTH - Prodanović, Danijela; Krivošej, Zoran; Stanojević, Miloš; Ćirić, Slavica (Bulletin of Natural Sciences Research, 2017)
This paper reports the chorological data on 3 internationally significant floristic species in Serbia, in the Ibar river valley, Kosovo and Metohija North. Those are: Gladiolus palustris Gaudin, Himantoglossum caprinum (M. Bieb) Spreng. and Narcissus poeticus subsp. radiiflorus (Salisb.) Baker. It also reports new research findings on a rare species of vascular flora of Serbia - Phlomoides tuberosa (L.) Moench. The distribution of the mentioned species is shown in UTM 10 km X 10 km squares, based on the field researches, herbarium collections inspections and literature data. As the studied species belong to the group of internationally important and rare species, the familiarity with the status of their populations and degree of their vulnerability would present a good basis for monitoring their protection both in Serbia and Europe.